Economic motives for the Ionian spread in Asia Minor - Hassan , Solaf; Al-Nouri, Maitham (Al-Adab Journal, 2024)
The period extending from 800-600 BC had witnessed the Greeks settling the western regions of Asia Minor, during which they developed many colonies and established powerful city-states that operated independently of their mother cities.There are many reasons that prompted the Greeks to establish colonies which were capable of economic growth, some of which included what had related to overpopulation in the mother country, others to the inability of the lands in the original Greek city-states to form a large city due to the terrain, while the areas that were colonized were wide and fertile, and the following research is an attempt To shed light on the economic reasons that were considered one of the motives for the Ionian colonization of the coasts of Asia Minor.